Purification and characterization of a pore-forming protein from the marine sponge Tethya lyncurium - Mangel, A. (2015)
A pore-forming protein was detected and purified for the first time from a marine sponge (Tethya lyncurium). The purified protein has a polypeptide molecular mass of 21 kDa and a pI of 6.4. Tethya pore-forming protein (also called Tethya hemolysin) rapidly lysed erythrocytes from a variety of organisms. After binding to target membranes, the hemolysin resisted elution with EDTA, salt or solutions of low ionic strength and hence resembled an integral membrane protein. Erythrocytes could be protected from hemolysis induced by Tethya hemolysin by addition of 30 mM dextran 4 (4-6 kDa; equivalent hydrodynamic diffusion radius, 1.75-2.3 nm) to the extracellular medium, but not by addition of uncharged molecules of smaller size [sucrose, raffinose and poly(ethylene glycol) 1550; equivalent hydrodynamic diffusion radii, 0.46, 0.57 and 1.2 nm, respectively]. This result indicates that hemolysin is able to form stable transmembrane pores with an effective diameter of about 2-3 nm. Treatment of osmotically protected erythrocytes with Tethya hemolysin caused a rapid efflux of intracellular K+ and ATP, and a rapid influx of extracellularly added Ca2+ and sucrose. In negative-staining electron microscopy, target erythrocyte membranes exposed to purified Tethya hemolysin displayed ultrastructural lesions but without visible pores.